2017
DOI: 10.22161/ijeab/2.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Alkali Delignification Coupled with Non-Ionic Surfactant Effect on the Fermentable Sugar Yield from Agricultural Residues of Cassava

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It was reported earlier that in the case of MW-assisted alkali-pretreated cassava leaves saccharified with Cellic alone without or with Tween 20 in the system, RS values of 41.60 and 46.23 g/L were, respectively, obtained (Pooja and Padmaja 2017), which showed that the effect of triple enzyme cocktail or detoxification chemical mix used in the present study was not highly significant for cassava leaves. MW-assisted dilute acid-pretreated cassava leaves on saccharification with triple enzyme (C + S + OBG) without (D0) or with (D+) detoxification chemical mix gave RS values of 30.28 and 33.95 g/L, respectively, after 120 h (Fig.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…It was reported earlier that in the case of MW-assisted alkali-pretreated cassava leaves saccharified with Cellic alone without or with Tween 20 in the system, RS values of 41.60 and 46.23 g/L were, respectively, obtained (Pooja and Padmaja 2017), which showed that the effect of triple enzyme cocktail or detoxification chemical mix used in the present study was not highly significant for cassava leaves. MW-assisted dilute acid-pretreated cassava leaves on saccharification with triple enzyme (C + S + OBG) without (D0) or with (D+) detoxification chemical mix gave RS values of 30.28 and 33.95 g/L, respectively, after 120 h (Fig.…”
Section: Discussionmentioning
confidence: 43%
“…However, when MW-assisted alkali-pretreated cassava stems were saccharified using Cellic alone with or without Tween 20, much lower RS contents were reported (Pooja and Padmaja 2017), which indicated that the triple enzyme cocktail was beneficial in enhancing RS release from MWassisted alkali-pretreated stems. Optimash BG used in the cocktail had component activities such as β-glucanase and xylanase, while Stargen had high amylolytic activity and these might have facilitated high hydrolysis of both hemicelluloses and starch.…”
Section: Saccharificationmentioning
confidence: 98%
See 3 more Smart Citations